Dinámica de crecimiento de biomasa aérea y aporte en servicios ambientales de especies forestales en plantaciones Puerto Almendra, Loreto-Perú, 2021 - Reátegui Amacenas, René (2024)
The study was carried out in the plantations of Cedrelinga cateniformis (Ducke) “tornillo” and Simarouba amara (Aublet) “marupa” of different ages located in the Forest Research and Teaching Center-Puerto Almendra of the Faculty of Forestry Sciences-UNAP, Iquitos -Peru, with the objective of quantifying the dynamics of biomass growth and its contribution to environmental services of commercial forest species in Puerto Almendra plantations, data on the trees present in each plantation were recorded and the growth of aerial biomass and contribution to environmental services of forest species, stored carbon, carbon sequestration and oxygen production have been quantified. It is reported that in the C. cateniformis plantation, greater dynamism of aerial biomass was found in the plantation of 41 years and 51 years of installation with an average of 1036.95 Kg/tree and 1293.29 Kg/tree with an increase of 25.29 Kg /tree years and 25.36 kg/tree/year; This shows that the ages of greatest production are between 41 years -51 years, while in S. amara, the greatest production of aerial biomass was determined in the 25-year-old plantation with 184 Kg/tree and an increase of 7.39 Kg /tree/year. Similarly, in carbon storage, sequestration of CO2 and O2 is greater at the same ages previously described and their analysis of variance for both species is significant, therefore, the alternative hypothesis proposed is accepted.